Civilian firearm injury and death in England and Wales. Issue 1 (4th November 2011) - Davies, M J; Wells, C; Squires, P A; Hodgetts, T J; Lecky, F E
Abstract : Introduction: There is currently concern in the UK that injuries and deaths caused by firearms are increasing. This is supported by small local studies but not by wider research to inform targeted prevention programmes. Methods: A retrospective analysis was performed of firearm injuries from the Trauma Audit and Research Network (TARN) database (1998–2007), the largest national registry of serious injuries. Data were analysed to determine temporal trends in the prevalence of firearm injuries and demographic characteristics of firearm victims. The UK Office of National Statistics provided data on all deaths by firearms as TARN does not record prehospital deaths. Results: Of 91 232 cases in the TARN database, 487 (0.53%) were due to firearm injury. There were 435 men and 52 women of median age 30 years. The median New Injury Severity Score in men was 18 with a mortality of 7.4%, compared with 15.5 and 3.8% for women. The highest rate of firearm injuries as a proportion of all injuries was submitted from London (1.4%), with the South East (0.23%) submitting the lowest rate. 90.5% resided in urban areas, 78% presented outside 'normal' hours and 90% were alleged assaults. As a proportion of all injuries submitted, a small upward trend in the prevalence of deaths due to firearms was demonstrated over the study period. An increase in homicides since 2000 was also noted with an increasingly younger population being involved. In contrast, data from the Office of National Statistics showed that the greatest number of deaths were self-inflicted rather than homicides (984 vs 527), with Wales having the highest number of such deaths and predominantly involving older men. Conclusions: Deaths and serious injuries caused by firearms remain rare in the civilian population of England and Wales, although an upward trend can be described. Victims of assault and homicide are predominantly young men living in urban areas and the population involved is getting younger. However, of all deaths, self-inflicted wounds are nearly twice as common as assaults, affecting predominantly older men living in more rural areas.